2016
DOI: 10.3390/nu8080505
|View full text |Cite
|
Sign up to set email alerts
|

Associations of Pre-Defined Dietary Patterns with Obesity Associated Phenotypes in Tehranian Adolescents

Abstract: Obesity has become a public health problem in adolescents and could be a risk factor for both short-term and long-term health consequences. This study aimed to evaluate the relationship of Dietary Guidelines for Americans Adherence Index (DGAI), Healthy Eating Index-2005 (HEI-2005) and Healthy Eating Index-2010 (HEI-2010) with risk of obesity associated phenotypes in Tehranian adolescents. This cross-sectional study was conducted within the framework of the Tehran Lipid and Glucose Study, on 722 adolescents, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 40 publications
0
9
0
Order By: Relevance
“… Not specified No Modified revised children’s diet quality index (M-RCDQI), Keshani et al (2018) [ 151 ] Food & nutrient Iran 1) FFQ Based on two previous studies [ 73 , 152 ] Reflects adherence to the 2005 Dietary Guidelines for Americans [ 140 ] and recommendations adjusted to better reflect the Iranian dietary patterns. 13 components, scored 0–90, points awarded & summed Not Specified No Dietary Guidelines for Americans Adherence Index (DGAI); Fogli-Cawley et al (2006) [ 153 ] developed in adults, Mohseni-Takalloo et al (2016) [ 154 ] used in adolescents. Food Iran 1) FFQ Reflects adherence to the Dietary Guidelines for Americans [ 140 ] 20 components, scored 0–20, calculated reported intake/ recommended intake, points awarded and summed.…”
Section: Resultsmentioning
confidence: 99%
“… Not specified No Modified revised children’s diet quality index (M-RCDQI), Keshani et al (2018) [ 151 ] Food & nutrient Iran 1) FFQ Based on two previous studies [ 73 , 152 ] Reflects adherence to the 2005 Dietary Guidelines for Americans [ 140 ] and recommendations adjusted to better reflect the Iranian dietary patterns. 13 components, scored 0–90, points awarded & summed Not Specified No Dietary Guidelines for Americans Adherence Index (DGAI); Fogli-Cawley et al (2006) [ 153 ] developed in adults, Mohseni-Takalloo et al (2016) [ 154 ] used in adolescents. Food Iran 1) FFQ Reflects adherence to the Dietary Guidelines for Americans [ 140 ] 20 components, scored 0–20, calculated reported intake/ recommended intake, points awarded and summed.…”
Section: Resultsmentioning
confidence: 99%
“…It was hypothesised that visceral fat is the main anatomic site for secretion of IL-6 ( 70 ) , and this inflammatory biomarker could stimulate CRP production by liver ( 71 ) . A cross-sectional study on 722 adolescents aged 10–19 years, indicated that participants in the highest quartile of healthy eating index-2010 had lower risk of central obesity than those in the lowest quartile ( 72 ) . The results of a cohort study conducted with the aim of examining the association of Dietary Approaches to Stop Hypertension (DASH) and the MetS on 425 Iranian children and adolescents demonstrated higher adherence to DASH diet was associated with lower abdominal obesity ( 73 ) .…”
Section: Discussionmentioning
confidence: 99%
“…Energy-dense nutrient-poor snacks, both salty and sweet, had undesirable effects on the incidence of MetS in Iranian children and adolescents [7, 10]. The World Health Organization (WHO) has issued dietary recommendations and guidelines on nutrition to help reduce the risk of chronic diseases and promote good health [11, 12], one of which is the Healthy Diet fact sheet [8] that includes practical advices on maintaining a healthy diet; recommending a shift in fat consumption away from SFAs to un-saturated fats and limiting total fat to less than 30% of total energy intake. Also this factsheet indicates elimination of free sugars to less than 10% of total energy intake and industrial trans-fats.…”
Section: Introductionmentioning
confidence: 99%